2013
DOI: 10.1007/s10517-013-2020-9
|View full text |Cite
|
Sign up to set email alerts
|

Original Nerve Growth Factor Mimetic Dipeptide GK-2 Limits the Manifestations of Hemorrhagic Stroke in Rats

Abstract: The protective effects of a new low-molecular-weight mimetic of nerve growth factor hexamethylene diamide bis-(N-monosuccinyl-L-glutamine-L-lysine; GK-2) were studied on the experimental model of hemorrhagic stroke (intracerebral posttraumatic hematoma) in rats. Intraperitoneal injections of GK-2 in a dose of 1 mg/kg 4 and 24 h after surgery and 24 h before testing the CNS function on days 3, 7, and 14 prevent death of experimental animals, reduce the neurological deficit, and normalized behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…In accordance, Ostrovskaya et al have demonstrated a neuroprotective effect of dipeptide in an in-vitro study (30). In this regard, other studies have indicated that dipeptides exhibit neuroprotective properties in various pathological conditions, including traumatic brain injury and hemorrhagic stroke models (31,32). (36).…”
Section: Hasegava Et Al Declared Neurotrophins Has An Important Role ...mentioning
confidence: 66%
“…In accordance, Ostrovskaya et al have demonstrated a neuroprotective effect of dipeptide in an in-vitro study (30). In this regard, other studies have indicated that dipeptides exhibit neuroprotective properties in various pathological conditions, including traumatic brain injury and hemorrhagic stroke models (31,32). (36).…”
Section: Hasegava Et Al Declared Neurotrophins Has An Important Role ...mentioning
confidence: 66%
“…In vivo experiments provided convincing evidence of the GK-2 neuroprotective effects. The efficacy of GK-2 was demonstrated in various models of Alzheimer’s disease (septo-hippocampal transection, cholinergic deficiency caused by prolonged administration of scopolamine, and on a model induced by administration of streptozotocin into the cerebral ventricles [23]), focal and global cerebral ischemia [24], and hemorrhagic stroke [25].…”
Section: Introductionmentioning
confidence: 99%